ANALISIS STRATEGI PEMASARAN DALAM RANGKA MENINGKATKAN VOLUME PENJUALAN PADA PT. INDOTRUCK UTAMA CABANG PEKANBARU - Putra, Faza Eka; Karneli, Okta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
In the company of heavy equipment, the role of business persons or companies very important as a determinant of the economy. As a company that sells heavy equipment are closely tied to consumer business in need of heavy equipment and consumer confidence to companies that provide a variety of promotions, product distribution channels smoothly, the price of the appropriate product quality and good products is necessary for consumers to be satisfied.This research was conducted at PT. Top Indotruck Pekanbaru Branch in order to determine whether the Marketing Strategy dimensions that promotional strategy, product strategy, price strategy and distribution strategy has been implemented well by PT. Top Indotruck Pekanbaru Branch so that it can be perceived by consumers PT. Top Indotruck Branch Pekanbaru is the consumer with the classification of individuals and companies. Source data used are primary data and secondary data or data obtained from PT. Indotruck Main Branch Pekanbaru. Collecting data using questionnaires and interviews. The population in this study are all consumers of up to 30 people by 2015.The research results are to be obtained results indicate that marketing strategy with distribution channel dimensions with good category, the promotion of good category, price categories, as well as products with very good category. And recapitulated in either category,only to be considered and improved Keywords : Marketing Strategy (promotion, product, price, and distribution), Heavy Equipment,Sales Volume